Biomechanical issues of tissue-engineered constructs for articular cartilage regeneration: in vitro and in vivo approaches. Issue 1 (19th December 2019) - Cipollaro, Lucio; Ciardulli, Maria Camilla; Porta, Giovanna Della; Peretti, Giuseppe M; Maffulli, Nicola
Abstract: Background: Given the limited regenerative capacity of injured articular cartilage, the absence of suitable therapeutic options has encouraged tissue-engineering approaches for its regeneration or replacement. Sources of data: Published articles in any language identified in PubMed and Scopus electronic databases up to August 2019 about the in vitro and in vivo properties of cartilage engineered constructs. A total of 64 articles were included following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Areas of agreement: Regenerated cartilage lacks the biomechanical and biological properties of native articular cartilage. Areas of controversy: There are many different approaches about the development of the architecture and the composition of the scaffolds. Growing points: Novel tissue engineering strategies focus on the development of cartilaginous biomimetic materials able to repair cartilage lesions in association to cell, trophic factors and gene therapies. Areas timely for developing research: A multi-layer design and a zonal organization of the constructs may lead to achieve cartilage regeneration.